Juego libre y la autonomía en niños de la institución educativa inicial N°847 Nuestra Señora de la Purísima, Punchana 2024 - Aquituari Aricari, Elsa Maritza (2025)
The objective of this research study is to determine the relationship between the level of free play application and the level of autonomy of three-year-old children of the Institution Educative Initial N°847 Nuestra Señora de la Purísima Punchana 2024. This research adheres to relational quantitative research approach whose design is non-experimental, transactional and correlational. The population under study is made up of 100 children enrolled in the Initial Educational Institution N°847 Nuestra Señora de la Purisima Punchana 2024. To obtain data, observation is used as a technique, and an observation guide as an instrument, which They are validated by three experts in the field; Likewise, reliability is carried out through the Inter correlation method of items whose coefficient is Cronbach's Alpha. The results show a Spearman correlation coefficient of 0.815 between the level of free play and the level of autonomy of the children, which indicates a positive and strong correlation between both variables. The bilateral significance level is 0.05. It is concluded that the null hypothesis is rejected and the general hypothesis is accepted. This confirms that there is a significant relationship between the level of free play and the level of autonomy of children.